Mediating Effect of Individuals’ Self-Efficacy on the Relationship between Digital Capability and Concern of Online Credential Adoption in Kuwait University - Alajmi, Hamad A S Z M; Ab Jalil, Habibah; Ismail, Suriani (Advances in Social Sciences Research Journal, 2025)
This study investigates the mediating effect of self-efficacy on the relationship between digital capability and concerns toward online credential adoption among faculty members at Kuwait University. As higher education increasingly transitions toward digital credentialing systems, understanding how faculty members’ perceive these technologies has become essential for successful implementation. Using quantitative design, data collected from faculty member at Kuwait Universityand analyzed through partial least squares structural equation modeling. The findings show that digital capability is a multidimensional construct encompassing ICT proficiency, information literacy, communication and collaboration skills, digital identity awareness, digital learning development, and creative problem-solving abilities. These capabilities influence faculty members’ concerns in distinct ways: identity-, literacy-, and ICT-related skills were associated with higher concerns, reflecting heightened awareness of privacy, security, and data protection risks, while creative and problem-solving skills reduced concerns by enhancing faculty members’ confidence in navigating digital platforms. Self-efficacy demonstrated a selective mediating role, significantly mediating some digital capability dimensions but not others, suggesting that confidence interacts differently with different types of digital skills. Overall, the model explained a substantial proportion of variance in concerns, underscoring the importance of digital capability and self-efficacy in shaping faculty members’ readiness to adopt online credentials. The study provides valuable insights for higher education institutions seeking to enhance digital preparedness, reduce adoption barriers, and build trust in emerging credentialing technologies.